PENGARUH KREATIFITAS PRODUK DAN INOVASI PRODUK TERHADAP KEPUASAN KONSUMEN DI STEAK HOUSE NOODLES - Sri Ernawati; Uty Kurniawati (ISOQUANT : Jurnal Ekonomi, Manajemen dan Akuntansi, 2020)
With the increasing number of restaurants, there is also increasing competition among restaurant entrepreneurs, they jointly compete in producing, gaining competitive advantage and providing value to their customers, wherever possible in accordance with the value expected by consumers. This study aims to analyze and test the effect of Product Creativity and Product Innovation both partially and simultaneously on Consumer Satisfaction at Steak House Noodles. This research was conducted in Bima City. This research is a survey research by distributing questionnaires with Likert scale measurement to 96 people who have visited Steak House Noodles. Data collection techniques using questionnaire, observation and study of literature, questionnaire distributed will be tested for validity and reliability then processed with SPSS 20. Data analysis using multiple linear regression. The results showed that product creativity affected Consumer Satisfaction at Steak House Noodles, Product Innovation affected Consumer Satisfaction at Steak House Noodles, and Product Creativity and Product Innovation significantly affected Consumer Satisfaction at Steak House NoodlesKey Word: Product Creativity, Product Innovation, Consumer Satisfaction